A Language Style Analysis of Press Release at The Walt Disney Company Website - Anindya, Nissa; Agustina, Hiqma Nur; Betari, Asa Wisesa (CV. Rustam, 2024)
This research was conducted with the aim of analyzing the language style employed in press statements issued by the Walt Disney Company, focusing on comprehending how this language style contributes to effective corporate communication. A qualitative descriptive methodology was applied, with the research drawing upon press statements available on Walt Disney's official website. The analysis of language style was based on the principles of sentence structure as outlined by Gorys Keraf, encompassing five distinct styles: climax, anti-climax, parallelism, antithesis, and repetition. The findings of this research revealed that repetition emerged as the predominant language style, accounting for 50% of the language styles identified, while anti-climax was the least frequently used, making up only 2%. This prevalence of repetition in press statements was observed to serve the purpose of reinforcing key messages, aiding reader recall, and ultimately facilitating more effective communication. This research explores how language style is important in business communication, using the well-known example of the Walt Disney Company. This research is looking at how the specific way language is used in their press statements helps them communicate better. These findings can be useful in different areas, like marketing, public relations, and business communication. Furthermore, this study demonstrates how analyzing language can help us understand the different styles companies use in their communication.